Development and implementation of an FPGA-based embedded real-time digital simulator - Sarac, Mehmet Riza; Aydogmus, Omur (Elsevier Sci Ltd, 2025)
This paper presents the development and implementation of a reconfigurable embedded real-time digital simulator system using an affordable Field Programmable Gate Array (FPGA) development board to simulate an RL circuit and a Permanent Magnet DC (PMDC) motor. These systems were selected for their fundamental structure, comprising essential components such as resistors (R) and inductors (L) for electrical systems, and friction (B) and inertia (J) in mechanical systems, along with the interactions between these components, which are widely used in modeling various circuits and systems. The real physical systems and their corresponding FPGA-based real-time digital simulators were operated concurrently under identical conditions. To evaluate the performance of the real-time digital simulators, the results from both the physical and simulator systems were compared and visualized using an oscilloscope. The latencies of the FPGA-based real-time digital simulators designed for this study were observed to be approximately 10 mu s for the RL circuit and 16 mu s for the PMDC motor. The total simulation time required by PC-based software simulators was measured to be around 5 to 20 ms for a 2 ms transient simulation of RL circuit and 2.08 s for a 0.2 s transient simulation of the PMDC motor. The focus on the RL circuit and PMDC motor in this study was chosen to enhance clarity and accessibility for researchers and practitioners. The methodology outlined in this paper provides a versatile framework that can be adapted to develop real-time digital simulators for a wide range of systems and applications.
Keywords: Embedded simulator; FPGA; Real-time digital simulator